Pembelajaran bahasa Arab yang inovatif dan kreatif - Kamalia, Karisma (Maliki Interdisciplinary Journal, 2023)
Student interest in learning Arabic is very minimal, because they feel bored and have difficulty learning Arabic. However, in essence, Arabic is a subject that must be mastered because as Muslims, it is certain that they are not far from Arabic in terms of worship and others. Therefore there is a need for innovation and creation in learning Arabic so that students become interested and enthusiastic in learning Arabic. This article was prepared using the method of conceptual analysis. By analyzing in depth the existing learning concepts and developing them to find new concepts in learning Arabic. With this there are innovations and creations in learning Arabic to make it easier for students to understand and master Arabic.